Functional Impairment and Periodontitis in Rheumatoid Arthritis - Hiroko Hashimoto; Shimpei Hashimoto; Yoshihiro Shimazaki (Elsevier, 2022)
Background: This study explored the association of functional impairment due to rheumatoid arthritis (RA) and RA disease activity with periodontal disease in patients with RA. Methods: Ninety-three patients with RA were included. Their RA functional status was assessed using the Steinbrocker classification. The serum level of matrix metalloproteinase-3 (MMP-3) was used as an indicator of RA disease activity. Probing depth (PD) and clinical attachment level (CAL) were used as indicators of periodontal status. We examined the association of RA severity and MMP-3 levels with periodontal status using a generalised linear model (GLM). Results: In a multivariate GLM, the coefficient for the mean PD was significantly positive in those with RA severity classes III or IV (reference: class I; β = 0.14; 95% confidence interval [CI], 0.03-0.25; P = .02) independent of other confounding variables. In multivariate GLM using the mean CAL as the dependent variable, the coefficient was significant in patients with high MMP-3 levels (10 ng/mL; β = 0.005; 95% CI, 0.001-0.008; P = .02). Conclusions: Functional impairment due to RA may affect PD, and high serum levels of MMP-3 may affect CAL.